Transition to Smart and Regenerative Urban Places (SRUP): contributions to a new conceptual framework - Peponi, Angeliki (2021)
Modern urbanism is called to face current challenges ranging from intensive demographic growth, economic and social stagnation to resources salvation and climate changes. Under the broader scope of sustainability, we argue that the transition to a holistic perspective of smart and regenerative planning and design is the way to face and yet to prevent these urban challenges. In doing so, we adopt systematic thinking to study the complexity of urban metabolisms at an urban place scale, emphasizing the ongoing coevolution of social-cultural-technological and ecological processes. Focusing on urban places, we give a city or region the sense of a place of stability, security, cultural and social interactions, and a sense of uniqueness. We plan and design innovative urban places that improve the environment and the quality of urban life, able to adapt and mitigate climate changes and natural hazards, leverage community spirit, and power a green-based economy. Designing the conceptual framework of smart and regenerative urban places we contribute to the field of modern urban studies helping practitioners, policymakers, and decision-makers to vision and adopt more environmental-friendly policies and actions using a user-centered approach.